The impact of creative thinking in cultural intelligence Field research on a sample of medical specialists - جثير, سعدون حمود; جثير, سعدون حمود; سعيد, سارة علي (Journal of Economics and Administrative Sciences, 2018)
Basic Orientation  and search path in determining the impact of creative thinking in cultural intelligence field research on the doctors competence, as is a theme of creative thinking great importance in spite of being a old , but his role at the individual level and / or organizational a sustainable effect toward developing a fact uncommon , any sense that one of the pillars of modernity and provide a unique future, as is the competitive weapon of the organizations in an environment dubbed fundamental change and provide all that is unfamiliar, and in the center of the field of research and objective measurement of creative thinking on doctors specialists at the construction of a state of the preference and loyalty of by auditors require to be with information on modern methods of providing medical service and provide grants to do their thinking creative both in regard to treatments or how to deal with auditors and in relation to medical examination, also it attracts cultural intelligence attention for its novelty and for being the ability and defensive ability and offensive at the same time to deal with cultural diversity, which has become the age feature specifically in the aftermath of the diversity of affected its effects with the adoptive category of culture and social class within the same country as the trend was the result of differing ideologies and ideas and the adoption of norms and values ​​even at the micro level and this led to find variations in the nature of preferences and the needs and requirements of the student medical service that in turn require the possession of knowledge culture Forever and fork them of subcultures, since owning a propensity to creative thinking is not enough for the success of doctors specialists in their field, but should enjoy the susceptibility and the ability to cultural intelligence in order to deal with this cultural diversity, and in this framework consisted sample of physicians jurisdiction in the Department of Health in the Rusafa and Karkh and Medical city has been the exclusion of the forensic medicine department because it does not include the profit area and have been using the questionnaire as a tool to collect data, reaching number (336), and Search for the existence and effect correlation between creative thinking and cultural intelligence had reacheddata, reaching number (336), and may reach search for the existence correlation and effect between creative thinking and cultural intelligence .